UPAYA MASYARAKAT DALAM MELESTARIKAN TEMBAWANG DI DESA MALO JELAYAN KECAMATAN TERIAK KABUPATEN BENGKAYANG - Asmeliati, Asmeliati; Idham, M; M, Iskandar A (JURNAL HUTAN LESTARI, 2020)
Tembawang is a land management carried out by the Dayak communities in West Kalimantan. One of the many in West Kalimantan is Tembawang Payut in Malo Jelayan Village, Teriak District, Bengkayang Regency. Most of the societies of Malo Jelayan Village use Tembawang to fulfill their daily needs by taking various types of results from the Tembawang such as fruits, vegetables, bamboo and so forth. This research examines the community's efforts in sustaining Tembawang in Malo Jelayan Village, Teriak District, Bengkayang Regency. The study was conducted for four weeks in the field. The technique used is a survey method with interview techniques and direct observation in the field. The sample was taken using a purposive sampling technique. Respondent participated comprised 30 people, including 17 men and 13 women. Data were analyzed using a qualitative descriptive approach. The results showed the community's efforts in preserving Tembawang in Malo Jelayan Village such as weeding by cleaning around Tembawang, works carried out in a traditional method (traditional ceremonies), replanting dead trees, as well as making an agreement between the people and the Village administrator to issue a permission for the outside community who wish to enter the Tembawang area.Keywords: Community, efforts, Malo Jelayan Village, Preservation, Tembawang.